Hot to trot eaudiobook - Beaton, M. C. (Agatha Raisin Mystery, 2020)
Beloved New York Times bestseller M. C. Beaton's cranky, crafty Agatha Raisin—now the star of a hit TV show—is back on the case again. When Private Investigator Agatha Raisin learns that her friend and one-time lover Charles Fraith is to be married to a mysterious socialite, Miss Mary Brown-Field, she sees it as her duty to find out what she can about the woman. Coming up empty, Agatha—out of selfless concern for Charles, of course—does the only sensible thing she can think of: she crashes their wedding, which ends in a public altercation. Nursing a hangover the next morning, she gets a phone call from Charles, with even more disturbing news: Mary has been murdered.Agatha takes on the case, and quickly becomes entrenched in the competitive equestrian world, in which Mary had been enmeshed—as well as the victim's surprisingly violent past. Agatha finds no shortage of motives among a wide range of characters, from Mary's old riding competitors, to enemies from her schoolgirl days, to her surly father, who threatens Agatha to mind her own business. Meanwhile, the police department has its money on another suspect: Agatha. Will she track down the criminal in time, or end up behind bars herself?